Impact of Antibiotic Shortage on H. Pylori Treatment: A Step-Wise Approach for Pharmacist Management - Michelle M. Lamb; Weiwei Wu; Ann Lloyd (University of Minnesota Libraries Publishing, 2013)
The current drug shortage crisis involving multiple oral antibiotics has significantly impacted preferred therapeutic options for treatment of H.pylori infection. Pharmacists may help alleviate the impact of this shortage through a proposed step-wise approach which includes proper inventory management, verification of indication, evaluation of regimen, therapeutic monitoring, and communication with patients and providers regarding alternative therapy or symptomatic relief.   Type: Original Research